Passive heating system of a residential building - P. S. Khujaev (Архитектура, строительство, транспорт)
In this article, we will talk about the passive heating system applied to residential buildings in rural areas. The air heating system is used as a heating surface in buildings with multi-channel structures in the fencing structures (external wall, ﬂoor and roof). In these cases, the author considers the issues of the ﬁrst and second conditions of temperature comfort, taking into account the temperature of the heating surface.